The Role of Institutional Collaboration Between Actors in Protecting the Economic Security of Indonesian Migrant Workers With Financial Literacy - Utami, Wulan Anggit; Rikza, Ayu; Anggresta, Pujana; Nuryananda, Praja Firdaus (Research and Development Agency Ministry of Home Affairs, 2022)
This study focuses on the collaboration between the Ministry of Education, Culture, Research and Technology of the Government of Indonesia, the Bhakti Jaya Indonesia Foundation, and the Universitas Pembangunan Nasional